Analysis of Marketing Mix on Durian Chips Sales at Souvenir Shops - Ulfa Mawadha; Robby Affendi; Ramadinda Risti (Smart International Management Journal, 2024)
Businesses encounter numerous challenges in managing and operating, one being the issue of effectively selling and distributing their products to meet consumer demand and access broader markets. Enhancing product quality is pivotal to fulfilling consumer needs. The study employs the Accidental sampling method, where individuals are chosen by chance if they meet specific criteria and encounter the researcher. A sample size of 67 individuals was utilized. Quantitative analysis was conducted using the multiple linear regression method, with data analyzed through the SPSS 17.00 program. Hypothesis testing results indicate that the calculated F value of 13.105 exceeds the F table value of 2.35, confirming the acceptance of the hypothesis. Consequently, the regression model demonstrates that product, price, promotion, and distribution collectively influence consumer behavior regarding the sale of durian cake at souvenir outlets. The R Square value of 0.443 suggests that 44.3% of the variance in consumer behavior can be attributed to these factors, with the remaining 55.7% potentially influenced by unexamined variables. Furthermore, the study reveals that product and promotion variables individually exert significant influence on durian cake sales at souvenir outlets. It is recommended that business leaders enhance and uphold strategies related to product quality and promotion to bolster sales